Evaluation of oncologic outcomes in head and neck cancer patients ≥80 years old based on adherence to NCCN guideline for postoperative adjuvant treatment. Issue 12 (12th September 2019) - Roden, Dylan; Daniels, Kelly; Metkus, James; Goldman, Richard; Walsh, Amanda; Johnson, Jennifer; Hamilton, James; Keane, William; Chapman, Andrew; Bar‐Ad, Voichita; Sweeny, Larissa; Curry, Joseph; et al.
Abstract: Background: There is a paucity of literature characterizing outcomes in older adult patients with head and neck cancer (HNC). This study aims to describe patients from this group, their adherence to National Comprehensive Cancer Network (NCCN) adjuvant treatment guidelines, and the impact of guideline adherence on overall survival (OS). Methods: In this retrospective cohort study, we reviewed all patients ≥80 years old with HNC who underwent surgery with curative intent from 2008 to 2016. Adherence to NCCN guidelines was determined in blinded fashion, and quality metrics and OS were compared. Results: One hundred fifty‐nine patients met inclusion criteria. The majority of patients (n = 94, 59%) underwent treatment in accordance with NCCN recommendations while 65 (41%) deviated from NCCN guidelines. The two cohorts did not demonstrate a difference in 2‐year OS (62% vs 66%, P = .50). Conclusion: Older adult patient outcomes were not different when treatment deviated from NCCN guidelines.